PECULIARITIES OF SOCIO-POLITICAL LEXICAL ACTIVITY IN LANGUAGE - Bakhtiyor Dilshatovich Bekmatov (Modern American Journals, 2025)
The specificity of socio-political lexical activity in language is largely determined by strong extralinguistic connections with the nominated events of objective reality. Therefore, the best way to systematize the identified socio-political dictionary and then express it is to present it in the form of interrelated thematic groups.
Keywords: Socio-political-lexicon, nomination, extralinguistic relations, lexical units.